George made a mistake in Step 2 when he incorrectly wrote the factors of the quadratic equation. Let's properly solve the equation step by step.
-
Start with the original equation: \[ x^2 + 4x - 5 = 7 \]
-
Rearrange the equation to set it to 0: \[ x^2 + 4x - 5 - 7 = 0 \implies x^2 + 4x - 12 = 0 \]
-
Now factor the quadratic equation \(x^2 + 4x - 12\): To find the factors, we need two numbers that multiply to -12 and add to 4. These numbers are 6 and -2. So, we can factor it as: \[ (x + 6)(x - 2) = 0 \]
-
Set each factor equal to 0: \[ x + 6 = 0 \quad \text{or} \quad x - 2 = 0 \]
-
Solve each equation: \[ x = -6 \quad \text{and} \quad x = 2 \]
What did George do wrong?
- George incorrectly factored the quadratic equation as \((x + 5)(x - 1)\) instead of the correct factors \((x + 6)(x - 2)\).
What are the correct solutions to the original equation? The correct solutions are: \[ x = -6 \quad \text{and} \quad x = 2 \]
List the smaller solution first:
- \(x = -6\) and \(x = 2\)